Gender, caste, and class in South India's technical institutions - Hebbar N., Nandini; Thapan, Meenakshi (New York : Oxford University Press, 2024)
With a wide arc encompassing the institutional big men, who run technical institutes and colleges, and the micro-politics of friendships and relationships, this book is a deep dive into the world of Indian engineering colleges. It juxtaposes the stark realities and lived experiences of students against the global sensibilities and standards to which such institutes lay claim. From the 1980s to the early 2000s, Tamil Nadu witnessed a record rise in the number of private engineering colleges. However, despite the manifold increase in the number of institutions and consequently, first-generation learners, hierarchies and inequalities continue to be reproduced in these almost temple-like institutions. Groups lacking the explicit markers of cultural and social capital struggle to find employment. By presenting perspectives on engineering students desires, anxieties, and processes of self-construction, the monograph examines how gender differences are reinforced through language, rules, regulations, surveillance, and control. In shifting the theoretical emphasis from subjects to subjectivities, Hebbar draws on the youths narratives of upward social mobility, crafting respectability, and notions of adulthood, holding a mirror to the fraught social scape of Indias private education sector.
Keywords: Caste-based discrimination -- India -- Tamil Nadu; Engineering students -- Social conditions -- India -- Tamil Nadu; Sex discrimination in higher education -- India -- Tamil Nadu; Technical institutes -- India -- Tamil Nadu